Individual differences influencing procedural learning outcomes in virtual reality: a case study on an exterior preflight inspection - Duruaku, Fiona; Sims, Valerie; Jentsch, Florian G. (Frontiers in Virtual Reality, 2025)
IntroductionVirtual reality (VR) has been increasingly used across safety-critical industries for training procedures because it allows for practice without real-world risks. Its effectiveness may be further influenced by individual differences. This paper examined technology features, including immersion and interactivity, and individual differences factors, specifically sex, spatial ability and personality traits, that could affect learning in VR, particularly within the context of procedural training. The study aimed to understand how VR functions and to identify who benefits most from its use.MethodsIn the experiment, 79 undergraduate students were trained to conduct an exterior preflight inspection of a passenger aircraft in VR, with varying levels of immersion (desktop PC vs. immersive VR) and interactivity (passive learning vs. active exploration). Participants were randomly assigned to one of four training groups: PC Passive, PC Active, VR Passive, and VR Active. The PC group used a mouse and keyboard, while the VR group used a head-mounted display and hand controllers to interact with the VR environment. Individual differences in sex, spatial ability, and personality traits were also investigated to determine their effects on procedural learning outcomes. Learning outcomes were assessed using two measures: a practical assessment using the desktop PC or immersive VR and a post-knowledge test. Data analyses were conducted using analyses of covariance (ANCOVAs) to examine the individual and combined effects of interactivity and immersion on procedural learning outcomes while controlling for pre-knowledge test scores. Additionally, stepwise multiple regression analyses were employed to evaluate the effects of individual differences on procedural learning.ResultsThe results indicated no difference in procedural learning outcomes across the levels of immersion and interactivity. Specific individual differences, including sex, and spatial ability, however, significantly predicted VR procedural learning outcomes.DiscussionOur findings challenge the assumption that higher immersion and higher interactivity alone, or in combination, always lead to better procedural learning outcomes. Furthermore, the study emphasizes the importance of considering individual differences when implementing VR in learning environments, as they play a critical role in shaping learning outcomes.